2021
DOI: 10.28991/esj-2021-01287
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Optimism Bias on Time and Cost on Construction Projects

Abstract: The unresolved scholarly debate to curtail cost and time performances in projects has led to alternate solutions, departing from the dominant technical school of thought to include concepts from behavioural sciences. In this paper, we consider the psychological effect, namely optimism bias, as one of the root causes for delays in cost overruns on projects. The research objectives were to determine the level of bias among project participants, rank time and cost overrun causes according to the participants’ bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…This view is inferred from the assumption that optimism bias is inherent in the nature of the sponsors and planners of a proposed transportation project. They are likely to inadvertently underestimate costs, time, and risks and overestimate benefits in the preparation of the overall pre-construction forecast (Chadee et al, 2021; Love & Ahiaga-Dagbui, 2018). The causal explanations that attribute the primary sources of cost overruns to the behavioral decision-making concepts of strategic misrepresentation and optimism bias are summarized as the Psycho-strategic school of thought (Ahiaga-Dagbui & Smith, 2014; Love et al, 2015b).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This view is inferred from the assumption that optimism bias is inherent in the nature of the sponsors and planners of a proposed transportation project. They are likely to inadvertently underestimate costs, time, and risks and overestimate benefits in the preparation of the overall pre-construction forecast (Chadee et al, 2021; Love & Ahiaga-Dagbui, 2018). The causal explanations that attribute the primary sources of cost overruns to the behavioral decision-making concepts of strategic misrepresentation and optimism bias are summarized as the Psycho-strategic school of thought (Ahiaga-Dagbui & Smith, 2014; Love et al, 2015b).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…A further review of the research design of the chosen articles found that similar in-depth investigations were adopted by Odeck and Kjerkreit (2019), Hayasaka et al (2018), and Love et al (2017). However, the review also observed that Chadee et al (2021) and Du et al (2019a) used Likert scale questionnaires to extrapolate the exhibition of optimism bias in project planners. Whereas current researchers in transport cost management are experiencing a shift from technical and engineering-managerial causal explanations to psychological and political explanations, they should priortize a methodological change in the field to elicit more systemic and insightful conclusions.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shu and Bazerman (2010), Mazutis and Eckardt (2017), Gifford (2011), Chadee et al (2021) Source: Personal elaboration.…”
Section: Single Action Bias and Illusion Of Being Rightmentioning
confidence: 99%
“…Optimism bias/ appraisal optimism [6,30,32,33,41,97,98,141] Overcommitment/ lock-in [9,30,54,142,143] Cautious attitude towards risks [54] Cognitive biases (e.g., anchoring, framing, Dunning-Kruger effect) [3,27,31,54,[134][135][136] Prejudices (discrimination, favouritism) [81,[144][145][146]…”
Section: Table 4 Critical Risk Group (Root Cause) -Psychological Cost...mentioning
confidence: 99%